Community Capabilities, Cultural Capital, Social Participation, Cultural Identity in the Economic Empowerment of Samosir as a National Super Priority Tourism Destination - Hervina Sihombing, Ester; Srie Hartati; Swanra Siamare-Mare (Sean Institute, 2025)
This study examines the roles of community capabilities, cultural capital, social participation, and cultural identity in driving the economic empowerment of local communities in Samosir as a National Super Priority Tourism Destination. The rapid development of tourism in strategic destinations often creates economic opportunities while simultaneously posing risks of social exclusion and cultural commodification if local communities are not actively involved. Using a mixed-methods approach, this research integrates quantitative data obtained from surveys of local tourism actors, micro and small enterprise owners, and community leaders, with qualitative insights from in-depth interviews and focus group discussions. The findings indicate that community capabilities—particularly skills, knowledge, and organizational capacity—have a significant positive effect on local economic empowerment. Cultural capital and cultural identity function not only as economic assets that enhance destination attractiveness but also as social resources that strengthen community cohesion and bargaining power. Furthermore, social participation mediates the relationship between community capabilities and economic empowerment, ensuring that tourism benefits are distributed more inclusively. This study contributes to the literature on community-based tourism by highlighting an integrated model of economic empowerment that places local culture and collective participation at its core. The results offer important policy implications for sustainable tourism development in Samosir and other super priority destinations, emphasizing the need to strengthen community capacity, protect cultural identity, and promote participatory governance to achieve inclusive and sustainable economic growth.